Fabrication And Electrical Characterization Of Silicon Bipolar Transistors In A O.5µm Based BiCMOS Technology. - Abdul Rahim, Alhan Farhanah; Abdul Rahim, Ahmad Ismat; Hashim, Md. Roslan; Mohd. Saari, Shahrul Aman; Ahmad, Mohd. Rais; Abdul Wahab, Mohd. Zahrin; Wan Adini, Wan Sabeng; Syono, Mohd. Ismahadi (2000)

(untitled)
Bipolar transistors are well known for its high current driving capability and current gains, while CMOS transistors are dominant in the integrated circuit market because of its low power consumption and small size advantage. The combination of both types of transistor on the same chip provides a high performance circuit with a high packing density. In this work 0.5-µm BiCMOS technology is fully utilized to realize silicon bipolar transistors with optimized performance. Preliminary electrical results are presented on bipolar transistors fabricated for the first time in Malaysia. Significant improvements in electrical device performance can be achieved by optimizing the emitter drive-in temperature and choice of annealing system.